2006
DOI: 10.1016/j.foreco.2006.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration changes in tree species abundance, diversity and structure in logged and unlogged subtropical rainforest over a 36-year period

Abstract: The long-term effects of logging treatments on rainforest regeneration are difficult to quantify due to compounding interactions with natural dynamics, site characteristics and tree species. The aim of this study was to examine regeneration differences over a 36-year period in stands subjected to various levels of disturbance ranging from natural, through an increasing intensity of individual tree removal to intensive logging. Multivariate and univariate analyses of trees !10 cm diameter at 1.3 m above the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 42 publications
1
30
0
1
Order By: Relevance
“…On the basis of assuming causal relationships between biodiversity, habitat heterogeneity, and ecosystem function, taxonomic species diversities in woodlands have often have been used to assess logging impacts. Several studies found no differences in species diversity between unlogged and logged forests (Verburg and van Eijk-Bos 2003, Kariuki et al 2006, Berry et al 2008, thereby arguing for compatibility between forest management practices and biodiversity conservation. However, the contrasting patterns of species diversity and functional diversity in the subtropical forest of this study suggest that the compatibility may not be evaluated appropriately by taxonomic diversity measures alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of assuming causal relationships between biodiversity, habitat heterogeneity, and ecosystem function, taxonomic species diversities in woodlands have often have been used to assess logging impacts. Several studies found no differences in species diversity between unlogged and logged forests (Verburg and van Eijk-Bos 2003, Kariuki et al 2006, Berry et al 2008, thereby arguing for compatibility between forest management practices and biodiversity conservation. However, the contrasting patterns of species diversity and functional diversity in the subtropical forest of this study suggest that the compatibility may not be evaluated appropriately by taxonomic diversity measures alone.…”
Section: Discussionmentioning
confidence: 99%
“…Devising sustainable forest management practices that are based on the retention of original communities and their component organisms is a pressing challenge for forest scientists and managers (Gustafsson et al 2012). Forest biodiversity has mostly been assessed using taxonomic information such as patterns of species richness (e.g., Verburg and van EijkBos 2003, Kubota et al 2004, Kariuki et al 2006, Lindenmayer et al 2006. However, to understand the cascading effects of biodiversity loss during forest conversions and to develop more sustainable management practices, forest ecologists need to determine how individual species contribute to ecosystem properties, such as structure, dynamic processes, and biophysical functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term studies of tree population dynamics are critical for understanding the conservation need of tropical forest ecosystems (Hubbell and Foster 1990;Condit 1995;Sheil et al 2000). Several longterm studies of tree population dynamics are available in both tropical and temperate forests (Lieberman and Lieberman 1987;Kochummen and Manokaran 1987;Foster and Hubbell 1992;Sukumar et al 1992;Balslev and Korning 1994;Bhat et al 2000;Lwanga et al 2000;Battles et al 2003;Takahashi et al 2003;Fashing et al 2004;Kariuki et al 2006;Baithalu et al 2012Baithalu et al , 2013. However, most studies on forest composition worldwide have been conducted on rain forest vegetation, and there are relatively few data available on tropical dry forest communities (Sussman and Rakotozafy 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Recent attention has advanced our focus beyond deforestation to forest degradation (Foley et al 2007;Putz & Redford 2008), especially logging, which impacts at least 15 000 km 2 of Amazonian forests per year (Asner et al 2005). Several authors have argued that the lack of decrease in tree species diversity they observed in selectively logged forests implies that logging activities are compatible with biodiversity conservation (Plumptre 1996;Cannon, Peart & Leighton 1998;Kariuki et al 2006;Berry et al 2008). These findings merit further evaluation given the ongoing development of metrics of functional diversity.…”
Section: Introductionmentioning
confidence: 99%